Gender discourses in the introductory books to Developmental Psychology - Souza, Leonardo Lemos [UNESP]; Fialho, Thais Souza [UNESP]; Nunes, Marcos Antonio Hoffmann; Botan, Alexandra Rosin [UNESP] (FapUNIFESP (SciELO), 2023)
The objective of this research was to identify and analyze the discourses about gender present in introductory books of the Developmental Psychology disciplines of undergraduate courses in Psychology, in Brazilian public universities. We identified, based on a consultation of the teaching plans of these courses, the two most cited books. We organize, examine and present the material, taking into account the procedures of documentary research: the context of production of the works, their authorship and the discourses about gender in the descriptions of age markers (childhood and adolescence). Based on the contributions of feminist and queer studies about gender and on the contributions of Michel Foucault on biopower, we identified possible effects of discourse about the control function and limitation of the ways of managing gender experiences in childhood and adolescence. We formulate considerations about these effects and the circumstance that training in the area approaches criticism of scientific discourse, from feminist and queer studies
Discursos de género en los libros introductorios a la Psicología del Desarrollo
DISCURSOS DE GÊNERO NOS LIVROS INTRODUTÓRIOS À PSICOLOGIA DO DESENVOLVIMENTO
Keywords: developmental psychology; discourse; gender